A case of posterior reversible encephalopathy syndrome associated with sepsis. (10th July 2018) - Garner, Orlando; Ramirez, Ana; Iardino, Alfredo
Abstract : Posterior reversible encephalopathy syndrome (PRES) is a neurological disorder characterised by parieto-occipital vasogenic oedema seen on MRI. Infection and sepsis has been reported as a possible cause for this disorder. We present a 19-year-old immunocompetent Caucasian man with known type 1 diabetes mellitus who presented to the emergency department with acute onset of bilateral visual loss, headaches and hypertension; he had been discharged 2 weeks ago for severe diabetic ketoacidosis and Staphylococcus aureus bacteraemia. Initial CT scan of the head was negative, but MRI showed findings suggestive of PRES. He was treated with nicardipine drip for strict blood pressure management and symptoms resolved within 4 days. PRES is a rare disease that has been increasingly reported as MRI becomes more commonplace. Usually associated with immunological disease, pre-eclampsia and cytotoxic therapies but an association with sepsis due to gram-positive bacteria.